2019
DOI: 10.4236/as.2019.102013
|View full text |Cite
|
Sign up to set email alerts
|

Soil Arthropod Abundance and Diversity Following Land Application of Swine Slurry

Abstract: Soil arthropods play an important role in nutrient cycling and maintenance of soil structure, and their abundance and diversity provide an indication of the biological quality of soil. Land application of livestock manure provides crop nutrients and may also impact the soil arthropod community. This study was conducted to quantify soil arthropod abundance and diversity for a period of one year following swine manure application via broadcast or injection. Arthropods were extracted from plot soil samples using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The application of swine manure generally increases SOC and SOM, although the exact increases are variable (Table 2). The lengths of the studies summarized in Table 2 ranged from 1 (Antoneli et al., 2019; Bao et al., 2013; Schuster et al., 2019) to 35 yr (Zhou et al., 2020). The reported SOC and SOM concentrations are highly variable, ranging from ∼4 (Bernal et al., 1992) to 64 g SOC kg −1 (Mbagwu et al., 1994) and from 8 (Shi et al., 2009) to 68 g SOM kg −1 (Bao et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of swine manure generally increases SOC and SOM, although the exact increases are variable (Table 2). The lengths of the studies summarized in Table 2 ranged from 1 (Antoneli et al., 2019; Bao et al., 2013; Schuster et al., 2019) to 35 yr (Zhou et al., 2020). The reported SOC and SOM concentrations are highly variable, ranging from ∼4 (Bernal et al., 1992) to 64 g SOC kg −1 (Mbagwu et al., 1994) and from 8 (Shi et al., 2009) to 68 g SOM kg −1 (Bao et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found in total K (Table 3). Total K ranged from 30 (Schuster et al., 2019) to 16,560 mg K kg −1 (Zhong et al., 2010). The increase in total K following swine manure application ranged from 4 (Xun et al., 2016) to 196% (Mbagwu et al., 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies report the use of this group as soil quality indicator, and often it is discussed together with other members of arthropod community [2,20]. In a study aimed to evaluate the effects of different swine manure applications on soil arthropod abundance and diversity, Pseudoscorpionida were more abundant in the injection treatment throughout most of the post-manure application period [24]. Çakir [6] showed that a natural disturbance, such as the one caused by the ant Formica rufa (Linnaeus, 1758), affected the abundance of this group negatively.…”
Section: Pseudoscorpionidamentioning
confidence: 99%
“…Moreover, this group's requirements are found in depth, under constant conditions of water and humidity [16,23]. On the other hand, in a study aimed to define the effects of different swine manure applications on soil arthropod abundance and diversity, Diplura showed not to be affected by the type of treatment [24].…”
Section: Introductionmentioning
confidence: 99%